Al Campbell and the Left: Building UAW/CAW Local 27 - Russell, Jason (Just Labour, 2011)
The role of the Left in unions, women’s activism, and the rise of industrial unions in the post-World War II decades have been the subject of valuable academic scrutiny. This article seeks to add to our understanding of these topics by looking at the role that one prominent activist—Al Campbell—played in building UAW/CAW Local 27 from the mid-1950s to the early 1970s. Campbell strongly advocated an independent Canadian autowork ers’ union, supported women’s activism, and was instrumental in helping expand a major composite local in the union. I argue in this article that, in order to understand the nature of the post-war Canadian labour movement, we need to devote greater attention to the role of devoted leftists in building local unions.